2016
DOI: 10.1007/s00117-016-0087-9
|View full text |Cite
|
Sign up to set email alerts
|

Moderne Bildgebung von Nierentumoren – Anwendung in Diagnostik und Therapie

Abstract: This article elucidates the various tools used for the diagnostics and characterization of renal lesions. The advantages and limitations of ultrasound, contrast-enhanced ultrasound (CEUS), computed tomography (CT) and magnetic resonance imaging (MRI) are presented and discussed. In addition, modern imaging features of CT and MRI, such as iodine quantification in CT as well as diffusion-weighted and perfusion imaging in MRI are presented. Lastly, recent developments in standardized reporting of renal tumors reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…There is increasing evidence to show that CT perfusion imaging is not only to measure changes in glomerular filtration [ 11 ] and evaluate angiogenesis [ 12 ], but also to monitor the response of tumors to treatment [ 13 , 14 ]. Several studies have demonstrated that multi-slice CT perfusion is a useful method for the evaluation of renal functions [ 8 , 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence to show that CT perfusion imaging is not only to measure changes in glomerular filtration [ 11 ] and evaluate angiogenesis [ 12 ], but also to monitor the response of tumors to treatment [ 13 , 14 ]. Several studies have demonstrated that multi-slice CT perfusion is a useful method for the evaluation of renal functions [ 8 , 15 17 ].…”
Section: Introductionmentioning
confidence: 99%